Incidência de malformações congênitas em crianças concebidas através de injeção intracitoplasmática de espermatozóides - De Araújo Filho, Edilberto [UNESP]; Carillo, Sonia Ventura; Silva, Patricia Gomes; Martinhago, Ciro Dresch; Baruffi, Ricardo Luiz Razera; Oliveira, João Batista Alcantara; Franco Junior, Jose Gonçalves [UNESP] (FapUNIFESP (SciELO), 2006)
Purpose: to evaluate the incidence and types of major congenital malformations (MCM) in liveborn children conceived by intracytoplasmic sperm injection (ICSI). Methods: a total of 680 liveborn children resulted from 511 couples submitted to ICSI from January, 1999 to December, 2002. Data collection of the children was performed through standardized questionnaire and clinical examination. Of the 511 couples, 366 had been contacted for a sampling of 371 gestations. Of the 680 liveborn, 520 had been evaluated, 250 of them (48.1%) through questionnaire and 270 (51.9%) through questionnaire and physical examination. Two hundred and fifty children were from singleton pregnancies and 270 from multiple pregnancies. Malformations were classified according to the 10th revision of the International Statistical Classification of Diseases and Related Health. Only MCM were analyzed in this study. The incidence of MCM was compared with that of the general population obtained by the Latin American Collaborative Study of Congenital Malformations. The statistical analysis was performed by the χ 2 test (level of significance p<0.05). Results: of the 520 children, 15 presented MCM, resulting in an incidence of 2.9%. There was no difference in relation to the control group (p>0.05), which showed 2.6% incidence of MCM. The most frequent malformations were of cardiac origin (four isolated and two associated), corresponding to 40% of the total. The other types of MCM were: renal (three), neural tube (two), skull (one), cleft lip (one), genital (one), Down syndrome (associated with cardiac malformations) (two), and musculoskeletal (one). Six MCM occurred in children from singleton pregnancies and nine in children from multiple pregnancies. Conclusion: the liveborn children conceived by ICSI presented incidence of major congenital malformations (2.9%) near to the expected for the general population (2.6%). However, to establish the risks of MCM with precision it is necessary to continue the evaluation of the children conceived by ICSI.
Incidence of congenital malformations in children conceived through intracytoplasmic sperm injection
Keywords: Abnormalities; Reprotuctive techniques, assisted; Sperm injections, intracytoplasmic